Low Doses of Eicosapentaenoic Acid and Docosahexaenoic Acid From Fish Oil Dose-Dependently Decrease Serum Triglyceride Concentrations in the Presence of Plant Sterols in Hypercholesterolemic Men and Women - Ras, Rouyanne T.; Demonty, Isabelle; Zebregs, Yvonne E.M.P.; Quadt, Johan F.A.; Olsson, Johan; Trautwein, Elke A. (The Journal of nutrition, 2014)
Plant sterols (PSs) lower LDL cholesterol (LDL-C) concentrations, whereas the n–3 (ω-3) fish fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) lower triglyceride (TG) concentrations. Incorporating both PSs and EPA+DHA from fish oil (FO) in a single food format was expected to beneficially affect 2 blood lipid risk factors. The aim of this study was to investigate the dose-response relation between low doses (<2 g/d) of EPA+DHA from FO, incorporated in a low-fat PS-enriched spread, and TG concentrations. In addition, effects on LDL-C were investigated. The study was designed as a randomized, double-blind, placebo-controlled parallel study. After a 4-wk run-in period, subjects were randomly assigned to consume either a control (C) spread (no PSs, no FO) or 1 of 4 intervention spreads containing a fixed amount of PSs (2.5 g/d) and varying amounts of FO (0.0, 0.9, 1.3, and 1.8 g/d of EPA+DHA) for 4 wk. Before and after the intervention, fasting blood samples were drawn for measuring serum lipids and EPA and DHA in erythrocyte membranes. In total, 85 hypercholesterolemic men and 247 women with a mean age of 57.9 y (range: 25–74 y) were included. Eighteen subjects dropped out during the study. At baseline, mean TG and LDL-C concentrations were 1.09 and 4.00 mmol/L, respectively. After the intervention, a significant dose-response relation for the TG-lowering effect of EPA+DHA [βln(TG) = −0.07 mmol/L per gram of EPA+DHA; P < 0.01] was found. Compared with the C group, TG concentrations were 9.3–16.2% lower in the different FO groups (P < 0.05 for all groups). LDL-C concentrations were 11.5–14.7% lower in the different PS groups than in the C group (P < 0.01 for all groups). EPA and DHA in erythrocyte membranes were dose-dependently higher after FO intake than after the C spread, indicating good compliance. Consumption of a low-fat spread enriched with PSs and different low doses of n–3 fatty acids from FO decreased TG concentrations in a dose-dependent manner and decreased LDL-C concentrations. This trial was registered at >clinicaltrials.gov as NCT01313988.